Diffusion imaging of nigral alterations in early Parkinson's disease with dopaminergic deficits. Issue 14 (11th August 2015) - Schuff, Norbert; Wu, I‐Wei; Buckley, Shannon; Foster, Eric D.; Coffey, Christopher S.; Gitelman, Darren R.; Mendick, Susan; Seibyl, John; Simuni, Tanya; Zhang, Yu; Jankovic, Joseph; Hunter, Christine; et al.
ABSTRACT: Background: This study reports the baseline characteristics of diffusion tensor imaging data in Parkinson's disease (PD) patients and healthy control subjects from the Parkinson's Progression Markers Initiative. The main goals were to replicate previous findings of abnormal diffusion imaging values from the substantia nigra. in a large multicenter cohort and determine whether nigral diffusion alterations are associated with dopamine deficits. Methods: Two hundred twenty subjects (PD = 153; control = 67) from 10 imaging sites were included. All subjects had a full neurological exam, a ( 123 I)ioflupane dopamine transporter (DAT) single‐photon emission computer tomography scan, and diffusion tensor imaging. Fractional anisotropy as well as radial and axial diffusivity was computed within multiple regions across the substantia nigra. Results: A repeated‐measures analysis of variance found a marginally nonsignificant interaction between regional fractional anisotropy of the substantia nigra and disease status ( P = 0.08), conflicting with an earlier study. However, a linear mixed model that included control regions in addition to the nigral regions revealed a significant interaction between regions and disease status ( P = 0.002), implying a characteristic distribution of reduced fractional anisotropy across the substantia nigra in PD. Reduced fractional anisotropy in PD was also associated with diminished DAT binding ratios. Both axial and radial diffusivity were also abnormal in PD. Conclusions: Although routine nigral measurements of fractional anisotropy are clinically not helpful, the findings in this study suggest that more‐sophisticated diffusion imaging protocols should be used when exploring the clinical utility of this imaging modality. © 2015 International Parkinson and Movement Disorder Society